Pengembangan Sistem Manajemen Risiko di Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kota Bontang berdasarkan Kerangka ISO 31000 - Wijdani Anindya Hadi; Putu Dana Karningsih (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2017)
Procurement is one of activity of government institution. ULP Bontang as a procurement unit is a part of Bappeda Bontang. Due to importance of procurement process, ULP Bontang needs to manage its risks by identifying, analyzing and controlling potential risk that may impedes ULP objectives. All goverment institution refer to a Internal Government Controlling System which called by Sistem Pengendalian Intern Pemerintah (SPIP) for conducting its risk management. Since there are several part of SPIP is not applicable in ULP Bontang. Therefore in this research, SPIP is modified based on ISO 31000 framework. Moreover, Delphi method is utilized to identiry riks involving five experts and established 23 potential risk in ULP Bontang. The modifications were also made in developing of severity and probability tables corresponding to the conditions of ULP Bontang. The formulation of mitigation recommendation concerned by very high potential risks. The mitigation for risk number (12) ULP Bontang office is not representative are securing ULP office using fingerprint device so only authorized personel allowed to enter the office. The cost required for this mitigation is about Rp 30.000.000 and Rp 32.000.000 for CCTV installation and evacuation route sign and also ULP needs to partnership with other institution to securing ULP Bontang member.